UPAYA DINAS PARIWISATA DAN KEBUDAYAAN KOTA BATAM DALAM KEGIATAN WISATA BELANJA DI KEPULAUAN RIAU (SUATU STUDI KUALITATIF) - Raja Riza Amanda Putri; I Gusti Agung Oka Mahagangga (JURNAL DESTINASI PARIWISATA, 2013)
ABSTRACT This research is about Efforts of Batam City Tourism and Cultural Office (Disparbud) to promote shopping tourism in Riau Archipelago. Shopping tourism as one of attractions that has competitive potency in Batam’s tourism. The Tourist attraction is expected to motivate foreign and domestic travelers to shop in Batam. In addition, through its activities is also able to maintain the stability and sustainability of development when the industry as an  ultimate key in the economy sector of Batam City is not running properly. The importance of this study to determine the form of attempt of Disparbud to promote shopping tourism and would like to know the function of shopping tourism promotion activities undertaken by Disparbud seen from direct observation and interviews. This study used a qualitative approach . Datas are used in this research is qualitative and quantitative data. Sources of data used in this study derived from primary data and secondary data. Data was collected by observation, indepth interviews, and documentation. Determination techniques with the base and the key informant technique. Data Analysis used in this research is a qualitative analysis in the form of descriptions. The results of this research showed that promotion activities shopping tourism by Disparbud Batam City has been implemented but not optimal. These because the implementation of such promotional activities encountered many obstacles in the field that should be of concern to all stakeholders and must be fixed. Forms of attempts of Disparbud Batam City to promote shopping tourism such as advertising activities, personal selling, sales promotion, public relations and direct marketing. Further, promotional activities are seen the function based on interviews, the real conditions in the field, and analyzed using concepts and theories.